2018
DOI: 10.4149/neo_2018_170507n328
|View full text |Cite
|
Sign up to set email alerts
|

Rapid screening test of most frequent BRCA1/BRCA2 pathogenic variants in the NGS era

Abstract: The average risk of breast cancer in general Slovak population of women is 4-5% and the risk of ovarian cancer is 2%. Probability of breast/ovarian cancer development is higher in individuals carrying a causative germline DNA variant in BRCA1 or BRCA2 gene responsible for hereditary breast/ovarian cancer (HBOC). Although a major proportion of inherited breast/ovarian cancers are due to the mentioned causal mutations, a number of new genes have emerged. Here we describe a rapid, multiplex and comprehensive appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The c.3700_3704del mutation was reported in Greece with a frequency between 0.3%–1.5% in breast and ovarian cancer cases [ 12 , 25 ]. Additionally, the mutation was observed in breast and ovarian cancer patients from Turkey, Germany, Denmark, Romania and Slovakia with a frequency between 0.2–0.9% [ 26 30 ]. The observation of the BRCA1 c.3700_3704del mutation in many different populations raise the question of whether it is an ancient mutation with single origin, or whether it has arisen several times in human history.…”
Section: Discussionmentioning
confidence: 99%
“…The c.3700_3704del mutation was reported in Greece with a frequency between 0.3%–1.5% in breast and ovarian cancer cases [ 12 , 25 ]. Additionally, the mutation was observed in breast and ovarian cancer patients from Turkey, Germany, Denmark, Romania and Slovakia with a frequency between 0.2–0.9% [ 26 30 ]. The observation of the BRCA1 c.3700_3704del mutation in many different populations raise the question of whether it is an ancient mutation with single origin, or whether it has arisen several times in human history.…”
Section: Discussionmentioning
confidence: 99%
“…Since the establishment of genetic testing of breast/ovarian cancer susceptibility genes among HBOC families in Slovakia, several studies related to this issue have been reported so far [31][32][33][34][35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…)del) and 4 different PV in BRCA2 (c.9403del, c.7595_7596ins, c.4005dup, c.3076A>T). According to the previous studies, six most frequent variants in the BRCA1 gene (c.68_69del, c.181T>G, c.3700_3704del, c.4243del, c.5329dup, c.843_846del) and four most frequent variants in the BRCA2 gene (c.3076>T, c.5645C>A, c.9098dup, c.9403del)account for the majority of BRCA1/2 mutation spectrum in Slovak HBOC families[38,39]. ,800 years ago in the region of Northern Europe, and spread to the various European populations, including the Ashkenazi Jewish population during the following centuries[48].…”
mentioning
confidence: 98%